2010
DOI: 10.1089/dna.2009.0971
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Extracellular DNA Using HypermethylatedRASSF1A,SRY, andGLOSequences—Evaluation of Diagnostic Possibilities for Predicting Placental Insufficiency

Abstract: This study evaluated quantification of fetal extracellular DNA in maternal plasma for differentiation between cases at risk of onset of placental-insufficiency-related complications and normal pregnancies. Using real-time polymerase chain reaction, fetal (sex-determining region Y [SRY] and hypermethylated RASSF1A sequence) and total (beta-globin [GLO] gene) extracellular DNA was examined in 70 normal pregnancies, 18 at risk of placental-insufficiency-related pregnancy complications, 24 preeclampsia with or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
2
17
0
1
Order By: Relevance
“…Similarly, our previous studies revealed significantly increased levels of extracellular fetal and total DNA in pregnancies with PE with or without IUGR (median 34 weeks, range 26-40 weeks), relative to controls (using SRY, hypermethylated RASSF1A sequence, and b-globin as markers and real-time PCR) (Hromadnikova et al, 2009(Hromadnikova et al, , 2010b. While increased levels of extracellular DNA were detected in pregnancies with PE w/or w/o IUGR relative to controls (RASSF1A p < 0.001; SRY p = 0.009; and GLO p < 0.001), quantities of fetal extracellular DNA in IUGR (median 28.5 weeks) were not statistically significant (RASSF1A p = 0.21; SRY p = 0.2).…”
Section: Extracellular Dna In Maternal Circulationsupporting
confidence: 65%
See 4 more Smart Citations
“…Similarly, our previous studies revealed significantly increased levels of extracellular fetal and total DNA in pregnancies with PE with or without IUGR (median 34 weeks, range 26-40 weeks), relative to controls (using SRY, hypermethylated RASSF1A sequence, and b-globin as markers and real-time PCR) (Hromadnikova et al, 2009(Hromadnikova et al, , 2010b. While increased levels of extracellular DNA were detected in pregnancies with PE w/or w/o IUGR relative to controls (RASSF1A p < 0.001; SRY p = 0.009; and GLO p < 0.001), quantities of fetal extracellular DNA in IUGR (median 28.5 weeks) were not statistically significant (RASSF1A p = 0.21; SRY p = 0.2).…”
Section: Extracellular Dna In Maternal Circulationsupporting
confidence: 65%
“…Lo et al (1999) showed a fivefold increase in the median concentration of extracellular fetal DNA, using realtime quantitative PCR assays for the SRY gene on the Y chromosome, in pre-eclamptic pregnancies (mean 32 weeks, range 27-41 weeks) compared with gestation age-matched controls). These data were later confirmed by other investigators using real-time quantitative PCR and either the SRY gene or the DYS-14 sequence as markers to differentiate between normal and complicated pregnancies (Smid et al, 2001;Zhong et al, 2001;Lau et al, 2002;Farina et al, 2004b;Engel et al, 2007;Alberry et al, 2009;Hromadnikova et al, 2009Hromadnikova et al, , 2010b. It was suggested that a rise in fetal DNA represented a valuable marker of placenta-related pregnancy complications, which could predict PE several weeks before clinical manifestation; however, with regard to IUGR, a rise in fetal DNA was less well correlated (Caramelli et al, 2003;Sekizawa et al, 2003;Farina et al, 2004c;Zhong et al, 2007;Hromadnikova et al, 2010b).…”
Section: Extracellular Dna In Maternal Circulationmentioning
confidence: 67%
See 3 more Smart Citations